Beta-lead oxide quantum dot (β-PbO QD)/polystyrene (PS) composite films and their applications in ultrafast photonics. Issue 14 (26th March 2019) - Ge, Yanqi; Huang, Weichun; Yang, Fumei; Liu, Jiefeng; Wang, Cong; Wang, Yunzheng; Guo, Jia; Zhang, Feng; Song, Yufeng; Xu, Shixiang; Fan, Dianyuan; Zhang, Han
Abstract : A waterproof β-PbO QD/PS composite film with strong nonlinear properties is developed as a saturable absorber for ultrafast pulse generation. Abstract : Polymer composite films, particularly those based on polymers and layered nanomaterials, are attractive materials for exploiting the properties of multiple materials for applications in electronics and photonics. In this work, a beta-lead oxide quantum dot (β-PbO QD)/polystyrene (PS) composite film is successfully fabricated by a solution blending method. The β-PbO QDs are well-distributed within a β-PbO QD/PS composite film and the composite film is transparent and flexible. Owing to the almost complete insolubility of both β-PbO QDs and PS, the as-fabricated β-PbO QD/PS composite film holds the nonlinear photonic response from 540 nm to 1060 nm under complete water immersion, confirming its excellent stability to high humidity. Additionally, the β-PbO QD/PS composite film exhibits a considerable capacity for optical modulation owing to a strong nonlinear absorption coefficient compared with those of other two-dimensional (2D) materials. On the basis of a home-made β-PbO QD/PS composite film saturable absorber, stable mode-locked pulses at 1060 nm are generated under humid conditions. It is anticipated that the β-PbO QD/PS composite films enable the exploitation of new waterproof, flexible photonic devices based on functional 2D materials and polymers.